DESAIN OP-AMP RAIL TO RAIL MENGGUNAKAN TEKNOLOGI CMOS 0.35µm - Erfiana Wahyuningsih; Hamzah Afandi; Dyah Nur‘ainingsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Op amp (Operating Amplifier) is a differential amplifier that has a large gain. Op amp is very flexible and easy to apply for various purposes. One is op amp rail to rail, compiled using 0.35u technology with adjusted W and L values to obtain the expected null offset value. Vdd and Vss's short-circuited voltage makes the op amp drive like a rail to a rail or a rail to rail. The output of the op amp rail to rail in the form of swing voltage or swing voltage defines how close the op-amp output can be driven to VDD or VSS (rail to rail). Keywords: Op amp, rail to rail, null offset